Giving voice to students and teacher: Uncovering collaboration difficulties and coping strategies in asynchronous online discussion - Wong, Shin Pyng * (2011)
Asynchronous online discussions such as forums, social networking sites and wikis have been widely used in various educational institutions. Some even utilise asynchronous online discussion as assessment of coursework. It is indicated in numerous studies that asynchronous online discussion can improve student-student or student-teacher interactions in ESL learning. Nevertheless, little attention is paid to the voices of the participants. Using narratives, this paper explores students' and teacher's collaboration difficulties and coping strategies in asynchronous online discussion. Participants include a university lecturer who teaches English for Specific Academic Purposes and three undergraduate students who major in Accounting, Finance and Business Studies, ranging from intermediate to advanced proficiency in English. The subjects took part in asynchronous online discussion for four weeks. Focus group interview and one on one interview were conducted. The narratives have implications for the design and implementation of asynchronous online discussion in ESL classroom.